Kihajar Dewantara's Views on Character Education and Its Relevance in the Learning of Faith and Morals in Elementary Madrasahs - Jarwo, Sujarwo; Muhamad Akip; Reni Marlina; Widia Putri (STIT Attaqwa, 2025)
The view of character education is indeed the main focus in building a quality generation. This study seems very relevant in the context of education in Indonesia, especially in the Madrasah Ibtidaiyah (MI) environment which has an important role in shaping children's character from an early age. The concept of character education according to Ki Hadjar Dewantara, as you explained, emphasizes the instillation of moral values ​​and noble character. The